Isolation and expression of human cytokine synthesis inhibitory factor cDNA clones: homology to Epstein-Barr virus open reading frame BCRFI. - Vieira, P (1991)
We have demonstrated the existence of human cytokine synthesis inhibitory factor (CSIF) [interleukin 10 (IL-10)]. cDNA clones encoding human IL-10 (hIL-10) were isolated from a tetanus toxin-specific human T-cell clone. Like mouse IL-10, hIL-10 exhibits strong DNA and amino acid sequence homology to an open reading frame in the Epstein-Barr virus, BCRFI. hIL-10 and the BCRFI product inhibit cytokine synthesis by activated human peripheral blood mononuclear cells and by a mouse Th1 clone. Both hIL-10 and mouse IL-10 sustain the viability of a mouse mast cell line in culture, but BCRFI lacks comparable activity in this assay, suggesting that BCRFI may have conserved only a subset of hIL-10 activities.